Pengaruh Peta Pemikiran dalam Pembelajaran Berbasis Masalah terhadap Penguasaan Konsep dan Literasi Sains Siswa SMP - Latifah Hanim; Herawati Susilo; Lia Yuliati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: This study aims to determine the effectiveness of PBL with thinking map on the mastery of the concept and students' scientific literacy in digestive system material, additives and addictive substances, and respiratory system in human. This quantitative study involved 94 students consisting of 3 classes, namely 31 students of class VIII C, 31 students of class VIII E and 32 students of class VIII A SMP Negeri 5 Jombang academic year 2018/2019. The results showed PBL assisted thinking map effective on mastering the concept of content dimensions and against scientific literacy in digestive system material, additives and addictive substances, and the respiratory system. The results of statistical tests showed that there were differences in the mastery of concepts and scientific literacy skills before and after using PBL assisted by thinking map on digestive system material, additives and addictive substances, and the respiratory system. The conclusion of this study is that problem-based learning assisted by thinking map has an effect on both mastery of science concepts and science literacy so that students are effectively used in junior high school on digestive system material, additives and addictive substances, and the respiratory system.Abstrak: Penelitian ini bertujuan mengetahui keefektifan PBM berbantuan thinking map terhadap penguasaan konsep IPA dan literasi sains siswa SMP pada materi sistem pencernaan, zat aditif dan adiktif, dan sistem pernapasan pada manusia. Penelitian kuantitatif ini melibatkan 94 peserta didik terdiri atas tiga kelas, yaitu 31 peserta didik kelas VIII C, 31 peserta didik kelas VIII E dan 32 peserta didik kelas VIII A SMP Negeri 5 Jombang tahun ajaran 2018/2019. Hasil penelitian menunjukkan PBM berbantuan thinking map efektif terhadap penguasaan konsep dan literasi sains pada materi sistem pencernaan, zat aditif dan adiktif, dan sistem pernapasan. Hasil uji statistik menunjukkan terdapat perbedaan penguasaan konsep dan kemampuan literasi sains sebelum dan setelah menggunakan PBM berbantuan thinking map. Kesimpulan penelitian ini adalah pembelajaran berbasis masalah berbantuan thinking map berpengaruh baik pada penguasaan konsep IPA dan literasi sains siswa sehingga efektif digunakan di SMP pada materi sistem pencernaan, zat aditif dan adiktif, dan sistem pernapasan.